Spatial Autocorrelation of Dengue Haemorrhagic Fever (DHF) Cases Using the Moran's Index Method in Muaro Jambi District, Indonesia - Muhammad Syukri; Rizalia Wardiah (GLOBAL HEALTH SCIENCE GROUP, 2023)
Dengue incidents in Jambi Province have spread to all districts/cities. Muaro Jambi Regency occupies the second position with the highest cases after Jambi Municipality. This study aims to determine the spatial autocorrelation of DHF cases in Muaro Jambi Regency in 2017–2021. The DHF cases analyzed in this study are case data recorded at the surveillance section of the Muaro Jambi Regency Health Office from 2017-2021. This study analyzed aggregate data from 22 working areas of community health centers in Muaro Jambi Regency. The software GeoDa 1.10 was used for analyzing the Global Moran Index and the Local Indicator for Spatial Autocorrelation (LISA). The results of the global moran's index analysis show that in 2017 (I=-0.400; p=0,001) and 2018 (I=-0,277; P=0,006) the pattern of distribution of DHF cases is spread , while in 2019 to 2021 the results of the analysis show that it is not significant. The results of the analysis using LISA found spatial autocorrelation of DHF cases in the High-High category (hotspots) in 2020 at the Tantan 1 Health Center. Areas with the Low-Low category (cold spots) in 2019 were found at the Kebon IX Health Center, and in 2021 at the Tempino Health Center.